2014
DOI: 10.1002/ange.201402011
|View full text |Cite
|
Sign up to set email alerts
|

Ester Carbonyl Vibration as a Sensitive Probe of Protein Local Electric Field

Abstract: The ability to quantify the local electrostatic environment of proteins and protein/peptide assemblies is key to yielding a microscopic understanding of many biological interactions and processes. Herein, we show that the ester carbonyl stretching vibration of two non-natural amino acids, L-aspartic acid 4-methyl ester and L-glutamic acid 5-methyl ester, is a convenient and sensitive probe in this regard since its frequency correlates linearly with the local electrostatic field for both hydrogen-bonding and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 47 publications
5
57
0
Order By: Relevance
“…), comparison between the Fourier transform infrared (FTIR) spectra of YGGCGG and YGGC * GG obtained in D 2 O also validates the successful incorporation of the ME group. This is because the YGGC * GG peptide, but not the YGGCGG peptide, gives rise to an IR band within the region of 1700–1750 cm −1 . As expected, this ester carbonyl stretching vibrational band is broad and peaked at about 1720 cm −1 , which is similar to that observed for a short peptide containing a D M residue, due to hydrogen‐bonding interactions with the solvent molecules …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…), comparison between the Fourier transform infrared (FTIR) spectra of YGGCGG and YGGC * GG obtained in D 2 O also validates the successful incorporation of the ME group. This is because the YGGC * GG peptide, but not the YGGCGG peptide, gives rise to an IR band within the region of 1700–1750 cm −1 . As expected, this ester carbonyl stretching vibrational band is broad and peaked at about 1720 cm −1 , which is similar to that observed for a short peptide containing a D M residue, due to hydrogen‐bonding interactions with the solvent molecules …”
Section: Resultssupporting
confidence: 77%
“…Recently, Pazos et al have shown that the ester carbonyl stretching vibration is a useful and convenient site‐specific IR probe of protein electrostatics because (1) its frequency is linearly correlated with the local electrostatic field, even when the carbonyl group is engaged in hydrogen‐bonding interactions; (2) its frequency is located in the spectral range of 1700–1800 cm −1 , wherein no intrinsic protein vibrations show up at neutral pH; and (3) it has a relatively high extension coefficient. In particular, Pazos et al have tested and demonstrated the utility of two ester‐containing non‐natural amino acids, l ‐aspartic acid 4‐methyl ester (hereafter referred to as D M ) and l ‐glutamic acid 5‐methyl ester (hereafter referred to as E M ), by incorporating them into various model peptide systems via solid‐phase peptide synthesis. In contrast, other non‐natural amino acid‐based IR probes, such as p ‐cyanophenylalanine and p ‐azido‐phenylalanine, have been incorporated into large proteins in vivo via amber codon suppression .…”
Section: Introductionmentioning
confidence: 99%
“…In a second example, Pazos et al (126) further showed that the C=O stretching frequency of two esters (i.e., methyl propionate and methyl acetate) afford similar spectroscopic properties as that of acetophenone. However, because the C=O stretching vibration of esters is typically in the range of 1710–1750 cm −1 , which decreases its spectral overlap with the amide I band of proteins, it offers certain advantages.…”
Section: Sidechain-based Ir Probesmentioning
confidence: 99%
“…Furthermore, vibrational solvatochromism can be used to systematically vary the field experienced by the probe in fluid solution, and the resulting spectral shifts can be related to the absolute electric field through MD simulations. 35 The separately measured Stark tuning rate (by VSS) provides a bridge between these two approaches. Additional computational methods have also been developed to determine the environmental effects on vibrational frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…1619 The carbonyl (C=O) vibration, which is generally more intense than nitriles, has been shown to vary linearly with electrostatic field in both H-bonding and non-H-bonding environments. 3, 5, 78, 20 The main limitation of the carbonyl probe is that its frequency overlaps with the densely populated amide I region in many biological systems. Fortunately, this can often be overcome by careful selection of a reference sample that is nearly identical to the sample of interest as well as isotopic labeling, or by using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%